SAMBAS CONVENTION CENTER - Nadiya, Nadiya; Caesariadi, Tri Wibowo; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Sambas Regency has the potential to improve the regional economy. There is industrial and business potential in Sambas Regency which makes it possible to increase meeting activities such as workshops, seminars, exhibitions, conventions, conferences, festivals and others. So far meeting activities in Sambas Regency have been carried out using makeshift facilities from other buildings, so they are inadequate to fulfill the special function of meetings. For this reason, it is necessary to provide facilities in the form of a convention center. The location of the Sambas Convention Center Design is on Jalan Ahmad Yani, Sambas City, Sambas Regency, West Kalimantan. The method applied in the design is the Glass box according to John Christopher Jones. Building design is carried out in several stages, namely by collecting primary data and secondary data. The data is then analyzed and produces a design concept that will realize the design of the building. The design function consists of meeting functions, commercial functions and service functions. The design results are in the form of design products in buildings with symmetrical shapes with the application of the theme of regionalism architecture. The building mass is inspired by the iconic building of Sambas City, namely the Sambas Palace with three separate mass arranged horizontally along the site area. The building is designed according to the architectural principles of local buildings. Building circulation is made flexibly according to the philosophy of Malay building. Using wide-span structures and grid structures in buildings and using trus systems in roof construction.